INOVASI PEMBELAJARAN PENDIDIKAN KREATIF ERA DISRUPTIF MENUJU MASYARAKAT 5.0 - Elphilia, Elphilia; Dikawati, Noepri (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2020)
Abstract— Innovation is an idea, idea, practice, or object that is considered new by humans or other adoption units . Through creative education learning innovations, students are free from feelings of laziness, bored or bored, fear of failure and feelings of being burdened because of the grace period of duty and so on. Learning in primary schools generally still strives for the ability to think rationally. The innovation process includes : seeing opportunities, implementing, reviewing ideas, issuing ideas.Keywords— Innovation, Creative Education, Disruftif Abstrak— Inovasi adalah gagasan, ide, praktik, atau objek yang dianggap baru oleh manusia atau unit adopsi lainnya. Melalui inovasi pembelajaran pendidikan kreatif, peserta didik terbebas dari perasaan malas, jenuh atau bosan, ketakutan akan kegagalan dan perasaan terbeban karena tenggang waktu tugas dan sebagainya. Pembelajaran pada sekolah dasar umumnya masih mengupayakan kemampuan berpikir rasional. Proses inovasi meliputi: melihat peluang, implementasi, megkaji ide, mengeluarkan ide.Kata Kunci—Inovasi, Pendidikan Kreatif, Disruftif